Financial market efficiency : symposia (2003)
Artículos: Burton G. Malkiel "The efficient market hypothesis and its critics". Robert J. Shiller "From efficient markets theory to behavioral finance"
Keywords: Mercado de capitales; Mercado financiero; Estados Unidos